Implementasi IP Forwarding Dengan Menggunakan IP Public Pada Alita Komputer Kota Blitar - Alviansyah, Alif; Sri Lestanti; Rizki Dwi Romadhona (ZETROEM, 2024)
Abstract - Alita Computer in Blitar is a company that specializes in computer service. According to a survey, the desired monitoring system for the company has not been realized because the data collection process and the format of reports processed by the administrators are not globally accessible. Therefore, customers are unable to view the status of processes via mobile devices on the internet.Thisresearch offers a solution to address this issue by establishing an online information web server accessible to customers through an external network. This web server will provide integrated monitoring with computer service data. The service provided involves utilizing IP forwarding with a public IP address, allowing the web server, which previously operated within a local network, to be accessed from external networks. In MikroTik devices, port forwarding is employed as a method to redirect data traffic from specific IP addresses and ports to other destination IP addresses and ports. Port forwarding using MikroTik is utilized to access servers or services in a local network from the internet.As a result of testing, the web server, initially located at IP address 192.168.100.100, was inaccessible to the public. However, after implementing IP forwarding with the public IP address 36.8.12.138, the web server became accessible even through external networks.